A Comparison of Game Based and Traditional Instructional Approaches: A Study of Physical Activity, Self-Determined Motivation and Enjoyment - Borhanadin Ghari; Hasan Mohammadzadeh; jalal Dehghanizade (University of Tehran, 2021)
The aim of this study was to investigate the effect of two instructional approaches (game based and traditional) on physical activity, self-determined motivation and physical activity enjoyment in university students who participated in physical education classes. This study was semi-experimental. The participants included 30 male university students (mean age 20.67±1.72 years) who were selected by convenience sampling method and randomly divided into two groups: game based instruction and traditional instruction. They participated in 18 sessions (for 6 weeks and 3 sessions a week) of basketball. The data were collected by the System for Observing Fitness Instruction Time, Beurer pedometer, Intrinsic Motivation Inventory, and Self-Determination Questionnaire. Descriptive statistics, independent t test, ANCOVA, and RANCOVA were used for analysis of data. The results showed significant differences between game based and traditional groups in the duration of moderate to high intensity physical activity and the number of steps (P≤0.001). There were no significant differences in physical activity enjoyment and a sense of competence between game based and traditional groups; But there were significant differences between two groups in autonomy (P≤0.001) and belonging (P≤0.013).The results showed that game based instructional approach can enhance physical activity level and quality of motivation of university students in physical education classes.